2017
DOI: 10.12691/education-5-7-17
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Decision Making and Teachers’ Commitment: A Comparative Study between Public and Private Secondary Schools in Arusha Municipality, Tanzania

Abstract: This study sought to find out about participation in decision making and teachers' commitment among secondary schools in Arusha city. It employed descriptive comparative design. A total of 159 teachers filled the questionnaires whose reliability was established through pilot study before actual data collection (See appendices). The study concluded that there is significant relationship between participation in decision-making and teachers' commitment. Teachers are committed to the success of their schools and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 7 publications
(8 reference statements)
1
5
0
3
Order By: Relevance
“…Teacher empowerment model (Short & Rinehart, 1992a). quantitative research of 159 teachers conducted in Arusha city secondary schools in Tanzania; the study was conducted to verify the link between engagement in decision-making and teachers' dedication; the results confirmed that teachers are committed to the success of their schools if they were involved in the decision-making process (Ngussa & Gabriel, 2017). Sarafidou and Chatziioannidis (2013), in a survey study of 143 primary school teachers in Greece, investigated teacher engagement in different fields of decision-making.…”
Section: Professional Growthmentioning
confidence: 94%
“…Teacher empowerment model (Short & Rinehart, 1992a). quantitative research of 159 teachers conducted in Arusha city secondary schools in Tanzania; the study was conducted to verify the link between engagement in decision-making and teachers' dedication; the results confirmed that teachers are committed to the success of their schools if they were involved in the decision-making process (Ngussa & Gabriel, 2017). Sarafidou and Chatziioannidis (2013), in a survey study of 143 primary school teachers in Greece, investigated teacher engagement in different fields of decision-making.…”
Section: Professional Growthmentioning
confidence: 94%
“…Categorically,the study gathered the following data: (1) the profile of the teacher respondents in terms of 1.1. sex; 1.2. age 1.3. years of teaching experience and 1.4. highest educational attainment; (2) the teacher respondents' assessment of their academic administrators' decisionmaking styles in terms of 2.1. directive decision making; 2.2. analytic decision making; 2.3 conceptual decision making; and 2.4. behavioral decision making; (3) the significant difference in the teacher respondents' assessment of their academic administrators' decision-making styles when their profiles are taken as test factors; (4) the teacher respondents' assessment of their empowerment in terms of the following factors: 4.1. decision making; 4.2. professional growth; and 4.3. autonomy; (5) the significant difference in the teacher respondents' assessment of their empowerment when their profiles are taken as test factors; (6) the significant relationship between the teacher respondents' assessment of their academic administrators' decision making and their empowerment (7) the observations of the academic administrators; and (8) The output of this research is to propose a program which aims at developing organizational leaders.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Collective decision-making improves the ability of education leaders to persuade others, form effective teams, resolve conflicts, and do away with conventional top-down leadership frameworks. According to Ngussa and Gabriel (2017), employee participation in leadership decisions and contributions can improve workers' job satisfaction. Employee involvement in group decision-making may help the company achieve its objectives by boosting morale, productivity, and the generation of creative and competitive ideas.…”
Section: Conceptual Frameworkmentioning
confidence: 99%